Effects of Differences in Lipid A Structure on TLR4 Pro-Inflammatory Signaling and Inflammasome Activation - Chilton, Paula M.; Embry, Chelsea A.; Mitchell, Thomas C. (Frontiers in Immunology, 2012)
The vertebrate immune system exists in equilibrium with the microbial world. The innate immune system recognizes pathogen-associated molecular patterns via a family of Toll-like receptors that activate cells upon detection of potential pathogens. Because some microbes benefit their hosts, mobilizing the appropriate response and then controlling that response is critical in the maintenance of health. TLR4 recognizes the various forms of lipid A produced by gram-negative bacteria. Depending on the structural forms of the eliciting lipid A molecule, TLR4 responses range from a highly inflammatory endotoxic response involving inflammasome and other pro-inflammatory mediators, to an inhibitory, protective response. Mounting the correct response against an offending microbe is key to maintaining health when exposed to various bacterial species. Further study of lipid A variants may pave the way to understanding how TLR4 responses are generally able to avoid chronic inflammatory damage.